2019
DOI: 10.3390/ma12182856
|View full text |Cite
|
Sign up to set email alerts
|

Alumina-Doped Zirconia Submicro-Particles: Synthesis, Thermal Stability, and Microstructural Characterization

Abstract: Zirconia nanoceramics are interesting materials for numerous high-temperature applications. Because their beneficial properties are mainly governed by the crystal and microstructure, it is essential to understand and control these features. The use of co-stabilizing agents in the sol-gel synthesis of zirconia submicro-particles should provide an effective tool for adjusting the particles’ size and shape. Furthermore, alumina-doping is expected to enhance the particles’ size and shape persistence at high temper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
2
9
0
1
Order By: Relevance
“…Therefore, they will be excluded from further discussion. The existence of ZrOx and oxygen vacancies, high concentrations of Al2O3 and metallic Al can affect the structural properties of ScAlSZ thin films [36,37]. The XRD measurement proves the previous assumption (Figure 4).…”
Section: X-ray Diffraction Patterns Show That 6scalsz Powder Hassupporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, they will be excluded from further discussion. The existence of ZrOx and oxygen vacancies, high concentrations of Al2O3 and metallic Al can affect the structural properties of ScAlSZ thin films [36,37]. The XRD measurement proves the previous assumption (Figure 4).…”
Section: X-ray Diffraction Patterns Show That 6scalsz Powder Hassupporting
confidence: 79%
“…Therefore, they will be excluded from further discussion. The existence of ZrO x and oxygen vacancies, high concentrations of Al 2 O 3 and metallic Al can affect the structural properties of ScAlSZ thin films [36,37]. The metallic Al or its compound phases in ScAlSZ thin films could form due to high Al concentration that exceed the solubility limit (~7 at.%) [30].…”
Section: X-ray Diffraction Patterns Show That 6scalsz Powder Hasmentioning
confidence: 99%
“…Especially, 3 and 5 mol% Al 2 O 3 can stabilize the grain size of ZrO 2 as 40‐45 nm even at temperature of 1273 K for 1 hour. Later, Dahl et al 71 performed more systematic investigations in ZrO 2 doped with Al 2 O 3 by expanding the range of dopant concentration (0‐50 mol%) and temperature (1073‐1473 K). They demonstrated that alumina accumulates near the grain boundaries; the reduction in GB energy and the pinning effect from the segregated Al 3+ should be responsible for the enhanced thermal stability of ZrO 2 .…”
Section: Proposal Of Thermo‐kinetic Correlationmentioning
confidence: 99%
“…It was reported that the dopant played a significant role in the densification behavior of ceramics by controlling the grain boundary mobility [53]. Higher sintering temperature was necessary to achieve full densification for Y-TZP with small alumina contents (0.01 wt.%) [54]. Moreover, even minor alumina addition could play an important role on the aging resistance of Y-TZP [55].…”
Section: Discussionmentioning
confidence: 99%